PITUTUR LUHUR–BASED CHARACTER EDUCATION FOR SOCIAL LIFE - Suwadi Suwadi (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
Character education programs often struggle to translate moral ideals into everyday social practice. Pitutur luhur—local moral sayings and guidance—offers culturally grounded resources for shaping students’ social conduct. Objective: This study explores how pitutur luhur values are internalized in school-based character education and how the process relates to students’ social life. Method: Using a qualitative descriptive design, data were collected through classroom and school observations, semi?structured interviews with teachers and students, and document review of lesson plans and school programs. Data were analyzed through iterative reduction, display, and theme development, supported by triangulation and member checking. Findings: Three main pathways supported internalization: (1) integration into classroom learning through contextual discussion and reflection; (2) habituation routines that repeatedly practice respect, responsibility, and cooperation; and (3) teachers’ exemplification as daily models of polite communication and fairness. Participants reported improvements in peer interaction, tolerance, and collaborative problem?solving, although limited instructional time and uneven initial awareness remained constraints. Conclusion: Embedding pitutur luhur in both instruction and school culture can strengthen students’ social life while sustaining local cultural heritage; continued school–family–community collaboration is essential for consistency.